2022
DOI: 10.1182/blood.2022017015
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal T-cell expansion in a patient with bone marrow failure after CD19 CAR-T therapy for Richter-transformed DLBCL

Abstract: The advent of chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment landscape of refractory B-cell malignancies. Real-world evidence has highlighted the high incidence of hematological toxicity, including prolonged and profound cytopenia. Here, we present a case of bone marrow (BM) failure in a 57-year old man with DLBCL-type Richter transformation receiving tisagenlecleucel in a standard-of-care setting. His clinical course was notable for underlying BM infiltration, severe cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In fact, a recent study focusing on stereotyped subset #2 and #169 (a satellite subset to subset #2) demonstrated shared SHM patterns in both subsets at either clonal or subclonal level, reflecting ongoing intraclonal diversification compatible with a branched evolution ( 98 ). The recently developed strategy to combine immunomics ( 99 ) with global transcriptomics in individual cells, allows for B cell and/or T cell clonotypes to be linked to gene expression signatures ( 100 ). Collectively, these technologies facilitate in-depth analysis of immunogenetic features (e.g., ongoing SHM and class-switching) at single-cell level and the discovery of clone-specific phenotypes, which may in turn expedite the identification of therapeutic targets and resistance markers.…”
Section: Deciphering Clonal Heterogeneity and Evolution In Cllmentioning
confidence: 99%
“…In fact, a recent study focusing on stereotyped subset #2 and #169 (a satellite subset to subset #2) demonstrated shared SHM patterns in both subsets at either clonal or subclonal level, reflecting ongoing intraclonal diversification compatible with a branched evolution ( 98 ). The recently developed strategy to combine immunomics ( 99 ) with global transcriptomics in individual cells, allows for B cell and/or T cell clonotypes to be linked to gene expression signatures ( 100 ). Collectively, these technologies facilitate in-depth analysis of immunogenetic features (e.g., ongoing SHM and class-switching) at single-cell level and the discovery of clone-specific phenotypes, which may in turn expedite the identification of therapeutic targets and resistance markers.…”
Section: Deciphering Clonal Heterogeneity and Evolution In Cllmentioning
confidence: 99%
“…Therefore, the composition of CAR-T cells’ preparation infused into patients possibly affects the efficiency of the therapy and only the products of precise cellular composition can provide uniform potency [ 30 ]. A case study by Rejeski et al [ 31 ] showed that different subpopulations of CAR-T cells not only have different biological functions but also show distinct differentiation patterns. In the presented study, the phenotype of CD4(+) CAR-T cells shifted from central memory to effector type, while CD8(+) CAR-T cells’ phenotype changed from effector memory to terminal effector cells.…”
Section: Reasons Behind Different Efficacy and Persistence Of Car-t C...mentioning
confidence: 99%
“…In the presented study, the phenotype of CD4(+) CAR-T cells shifted from central memory to effector type, while CD8(+) CAR-T cells’ phenotype changed from effector memory to terminal effector cells. Yet, at the same time, both subpopulations of CAR-T cells underwent equivalent clonal expansion [ 31 ].…”
Section: Reasons Behind Different Efficacy and Persistence Of Car-t C...mentioning
confidence: 99%
“…[9][10][11] Real-world evidence has further emphasized the importance of hematological toxicity as the most common high-grade toxicity of CAR-T therapy, which can present both as a syndrome of profound bone marrow aplasia, 12 or as prolonged cytopenia. [13][14][15][16][17][18] An additional expected on-target/off-tumor side effect of CD19-directed CAR-T is B-cell aplasia and hypogammaglobulinemia. 19 The combination of cellular and humoral immunodeficiency translates into a predisposition for infectious complications, which substantially contribute to the toxicity burden and drive nonrelapse mortality.…”
Section: Introductionmentioning
confidence: 99%